Modulating fear extinction memory by manipulating SK potassium channels in the infralimbic cortex - Criado-Marrero, Marangelie; Santini, Edwin; Porter, James T. (Frontiers in Behavioral Neuroscience, 2014)
Fear extinction correlates with increased infralimbic (IL) neuronal excitability. Since small conductance Ca2+-dependent K+ (SK) channels modulate neuronal excitability and certain types of learning and memory, pharmacological modulation of SK channels could be used to regulate IL excitability and fear extinction. To test this, we first determined the effect of blocking SK channels with apamin on the intrinsic excitability of IL pyramidal neurons in brain slices. In whole-cell patch-clamp recordings, apamin increased the number of spikes evoked by a depolarizing current pulse, increased the firing frequency, and reduced the fast afterhyperpolarizing potential (fAHP) indicating that blockade of SK channels could be used to enhance the intrinsic excitability of IL neurons. Next, we assessed whether SK channels in IL regulate extinction of conditioned fear by infusing apamin into IL of fear conditioned rats prior to extinction training. Apamin infusion did not affect conditioned freezing at the beginning of the extinction session or within-session extinction. However, the following day, apamin-infused rats showed significantly less conditioned freezing. To further examine the importance of SK channels in IL in fear extinction, we assessed the effect of the SK channel activator DCEBIO on IL neuronal excitability and fear extinction. Activation of SK channels with DCEBIO decreased the number of evoked spikes, reduced the firing frequency, and enhanced the fAHP of IL neurons. Infusion of DCEBIO into IL prior to fear extinction impaired recall of fear extinction without affecting acquisition of extinction. Taken together, these findings suggest that SK channels are involved in regulating IL excitability and extinction-induced plasticity. Therefore, SK channels are a potential target for the development of new pharmacological treatments to facilitate extinction in patients suffering from anxiety disorders.